GLOBAL-SCALE INTERACTIONS BETWEEN THE SOLID EARTH AND ITS FLUID ENVELOPES AT THE SEASONAL TIME SCALE - Cazenave A.; Mercier F.; Bouille F.; Lemoine J.M. (My University, 1999)
Changes in the mass distribution inside the surface fluid envelopes in response to climate changes affect the Earth by changing its gravitational field, its rotation and the position of its centre of mass. At subdecadal time scales, temporal changes of these global Earth parameters are now currently determined by space geodesy. Here we focus on annual variations which carry the largest energy. We combine space geodesy-derived annual variations of the centre of mass position, rotation pole position and dynamical flattening, allowing us to map annual variations of the long-wavelength geoid. Annual amplitude maxima amounting to 5 mm are located over continental regions of the Northern Hemisphere. These variations result from seasonal transfers of air and water mass among atmosphere, oceans, continents and ice sheets as evidenced by a comparison with the annually varying geoid deduced from hydrometeorological loading data (atmospheric surface pressure, snow and soil moisture load, ocean mass load).
Keywords: GEODESY; GRAVITY FIELD; POLAR WANDERING; MASS; GLOBAL CHANGE